Identification ratio of Si/Ti and Ca/Ti content by X-Ray Fluorescence in tsunami soil samples - LAHNA, KURNIA; MITAPHONNA, RARA; RAMLI, MULIADI; ISBAH, FALIQUL; YUSIBANI, ELIN; FAUZI, FAUZI; ISMAIL, NAZLI; IDRS, NASRULLAH (Universitas Syiah Kuala, 2024)
Earthquakes and tsunamis natural disasters have repeatedly occurred on the coast of Aceh province, which lies between the confluence of two plates. The tsunami deposits in this area can provide important information regarding the reconstruction of marine attacks by past earthquakes and tsunamis. In general, tsunami deposits can be identified based on their geological, sedimentological, paleontological, and geochemical characteristics. In our research work, spectrometry X-ray fluorescence (XRF) has been utilized to investigate the geochemical signatures of tsunami-affected soil samples in Aceh province at three tsunami-impacted areas, namely Aceh Besar regency, Banda Aceh City, and Aceh Barat regency. The sampling point is located about a kilometer from the coastal line. Our findings indicate that tsunami-affected soils in Aceh Province after 10 years struck by tsunami contain terrestrial markers such as Fe and Ti, carbonate markers (Mg, Ca), and heavy metals elements (Cr, Ni, Cu, Zn, and Sr). On the other hand, in our study, the concentration ratios of several elements such as Si/Ti and Ca/Ti seem most suitable as a chemical signature for differentiating environmental conditions such as the 2004 Indian Ocean tsunami event. It could be noticed that geochemical analysis by XRF can be applied to characterize the tsunami-affected soils in several coastal areas of Aceh province.